Reflections on the optimal size of government - Hans G. Monissen (University of Würzburg, Department of Economics, 1999)
It is not always easy to see a common thread in Tullock's work: he is almost too fertile and throws off so many ideas in all directions that the connecting links between them threaten to disappear from view. Any simple summary of his 'system', therefore, must wait on some future effort of his own. However, a common thread in his work, as in that of all public choice theorists, is the view that human behaviour must be viewed in all circumstances as a 'rational' response to the twin constraints of the physical environment and the prevailing social institutions; people will always strive to maximize their satisfactions in the face of these constraints, taking due account of the costs of alternative choices (Blaug, [1985] 252-53). Gordon Tullock is the 1998 Distinguished Fellow of the American Economic Association. In the enclosed short appreciation of his work we read: Tullock's scholarship and entrepreneurship have left an indelible imprint on economics. He is a pioneer who has worked almost exclusively at the frontiers of the discipline (American Economic Review, [1998]). Inspecting Gordon Tullock's curriculum vitae which contains 37 pages compiling his published work will indeed confirm the assertion that his scientific work is concentrated at the frontiers of our discipline. However, Tullock has not only extended the domain of economic inquiry, but also strengthened the core of our discipline. As opposed to Blaug's remark we should note that there exists a simple summary of his system. It was in 1975 when Gordon Tullock with his co-author Richard McKenzie published one of the most fascinating introductory textbooks in economics which exposes the authors' view of the workings of the socio-economic process. In their standard model the basic unit of analysis used is homo oeconomicus as characterized above. The authors apply this role model consistently and successfully to a wide range of both market and non-market phenomena. The paper Reflections on the Optimal Size of Government should, at least subjectively, reflect Gordon Tullock's influence on our perspective. However, we have to admit our analytical shortcomings of not being able to simultaneously include such Tullockian topics as rent-seeking, demand-revealing, bureaucratic behavior (to name only some of his important insights) into an envisaged general-equilibrium model.
Keywords: 330; Staatsquote; Leviathan-Modell; Public Choice; Optimale Besteuerung; Theorie